How are ECG parameters related to cardiac magnetic resonance images? Electrocardiographic predictors of left ventricular hypertrophy and myocardial fibrosis in hypertrophic cardiomyopathy. Issue 5 (23rd April 2020) - Dohy, Zsofia; Vereckei, Andras; Horvath, Viktor; Czimbalmos, Csilla; Szabo, Liliana; Toth, Attila; Suhai, Ferenc I.; Csecs, Ibolya; Becker, David; Merkely, Bela; Vago, Hajnalka
Abstract: Background: Structural myocardial changes in hypertrophic cardiomyopathy (HCM) are associated with different abnormalities on electrocardiographs (ECGs). The diagnostic value of the ECG voltage criteria used to screen for left ventricular hypertrophy (LVH) may depend on the presence and degree of myocardial fibrosis. Fibrosis can cause other changes in ECG parameters, such as pathological Q waves, fragmented QRS (fQRS), or repolarization abnormalities. Methods: We investigated 146 patients with HCM and 35 healthy individuals who underwent cardiac magnetic resonance imaging (CMR; with late gadolinium enhancement [LGE] in HCM patients) and standard 12‐lead ECGs. On the ECG, depolarization and repolarization abnormalities, the Sokolow–Lyon index, the Cornell index, and the Romhilt–Estes score were evaluated. The left ventricular ejection fraction, volumes, and myocardial mass (LVM) were quantified. Myocardial fibrosis was quantified on LGE images. Results: The sensitivity of the Romhilt–Estes score was the highest (75%), and this hypertrophy criterion had the strongest correlation with the LVM index ( p < .0001; r = .41). The amount of fibrosis was negatively correlated with the Cornell index ( p = .015; r = −.201) and the Sokolow–Lyon index ( p = .005; r = −.23), and the Romhilt–Estes score was independent of fibrosis ( p = .757; r = 0.026). fQRS and strain pattern predicted more fibrosis, while the Cornell index was a negative predictor of myocardial fibrosis ( p < .0001). Among others, the strain pattern was an independent predictor of the LVM ( p < .0001). Conclusion: The Romhilt–Estes score is the most sensitive ECG criterion for detecting LVH in HCM patients, as myocardial fibrosis does not affect this criterion. The presence of fQRS and strain pattern predicts myocardial fibrosis.